Visualizing Dynamic Changes at the Maternal-Fetal Interface Throughout Human Pregnancy by Mass Cytometry - van der Zwan, Anita; van Unen, Vincent; Beyrend, Guillaume; Laban, Sandra; van der Keur, Carin; Kapsenberg, Hanneke J. M.; Höllt, Thomas; Chuva de Sousa Lopes, Susana M.; van der Hoorn, Marie-Louise P.; Koning, Frits; Claas, Frans H. J.; Eikmans, Michael; et al. (Frontiers in Immunology, 2020)
During healthy pregnancy a balanced microenvironment at the maternal-fetal interface with coordinated interaction between various immune cells is necessary to maintain immunological tolerance. While specific decidual immune cell subsets have been investigated, a system-wide unbiased approach is lacking. Here, mass cytometry was applied for data-driven, in-depth immune profiling of the total leukocyte population isolated from 1st, 2nd, and 3rd trimester decidua, as well as maternal peripheral blood at time of delivery. The maternal-fetal interface showed a unique composition of immune cells, different from peripheral blood, with significant differences between early and term pregnancy samples. Profiling revealed substantial heterogeneity in the decidual lymphoid and myeloid cell lineages that shape gestational-specific immune networks and putative differentiation trajectories over time during gestation. Uncovering the overall complexity at the maternal-fetal interface throughout pregnancy resulted in a human atlas that may serve as a foundation upon which comprehension of the immune microenvironment and alterations thereof in pregnancy complications can be built.